2022
DOI: 10.1177/00027162221109992
|View full text |Cite
|
Sign up to set email alerts
|

Why Do People under Community Supervision Work and Earn So Little? And What Can Policy Do to Increase Their Employment and Earnings?

Abstract: In this article, I review what we know about the impacts of felony convictions and incarceration on later employment and earnings, particularly for those under community supervision. I then discuss what employers and public policymakers can do to improve these outcomes. First, I review the basic empirical facts on the employment and earnings of returning citizens, various hypotheses that could explain these facts, and the available evidence that support those hypotheses. Second, I review why people under commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…In addition to these restrictions, research indicates that employers are less willing to hire individuals with a history of incarceration than those without, even when equating work credentials and experience (Larson et al, 2022; Pager, 2003). For re‐entering citizens who do find work, they are more likely to be hired for low‐wage jobs than adults without a felony conviction, employment that is not effective at reducing poverty or recidivism (Holzer, 2022; LaBriola, 2020). Research has shown that recently released individuals are at an increased risk for death (Binswanger et al, 2007), with Black re‐entering individuals returning to areas characterized by greater disadvantage, including poverty and housing instability (Harding et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these restrictions, research indicates that employers are less willing to hire individuals with a history of incarceration than those without, even when equating work credentials and experience (Larson et al, 2022; Pager, 2003). For re‐entering citizens who do find work, they are more likely to be hired for low‐wage jobs than adults without a felony conviction, employment that is not effective at reducing poverty or recidivism (Holzer, 2022; LaBriola, 2020). Research has shown that recently released individuals are at an increased risk for death (Binswanger et al, 2007), with Black re‐entering individuals returning to areas characterized by greater disadvantage, including poverty and housing instability (Harding et al, 2013).…”
Section: Introductionmentioning
confidence: 99%